2013
DOI: 10.1007/s00432-013-1430-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the XPC (A2920C), XPF (T30028C), TP53 (Arg72Pro) and GSTP1 (Ile105Val) polymorphisms in the risk of cutaneous melanoma

Abstract: Our data suggest that inherited abnormalities of XPC, XPF, TP53 and GSTP1 pathways of the DNA repair, apoptosis and metabolism of reactive oxygen species are important determinants of CM in individuals from south-eastern Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
0
19
0
2
Order By: Relevance
“…A total of 81 studies were retrieved through database searching. After reading the titles and abstracts, nine potential studies were identified for further investigation . One case–control study was excluded for being not consistent with HWE .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 81 studies were retrieved through database searching. After reading the titles and abstracts, nine potential studies were identified for further investigation . One case–control study was excluded for being not consistent with HWE .…”
Section: Resultsmentioning
confidence: 99%
“…One case–control study was excluded for being not consistent with HWE . Finally, eight studies were included for data extraction . The studies were published between 2005 and 2013 (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already well established that abilities to DNA damage repair are variable in humans and may affect CM susceptibility [13][14][15]. The XPC single nucleotide polymorphism (SNP) with an A>C substitution at nucleotide 2920 (Lys939Gln) was associated with a lower function of the encoded protein of DNA damage repair in peripheral blood lymphocytes challenged by mutagens and gamma radiation [16].…”
Section: Introductionmentioning
confidence: 99%
“…rs1042522 polymorphism is located in exon 4 of p53 gene, in which an arginine (Arg)gproline (Pro) amino acid substitution is present at amino acid position 72; such polymorphism is commonly named Pro72Arg or codon polymorphism (Ara et al, 1990). Epidemiological studies have indicated that p53 Arg72Pro polymorphism increases the risk of many cancers, such as cutaneous melanoma (Oliveira et al, 2013), bladder cancer (Xu et al, 2012), and nasopharyngeal carcinoma . However, two meta-analyses have failed to identify a significant association between p53 Arg72Pro polymorphism and oral cancer Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%